EVOLUTION OF CANADIAN SYSTEM FOR GEOSCIENCE DATA, 1964-73 (EVOLUTION DU SYSTEME CANADIEN DE DONNEES GEOSCIENTIFIQUES, 1964-73) - Burk, Jr., Cornelius F. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF